The void fraction and frictional pressure drop of upward two-phase flow under high pressure brine condition. (15th March 2023) - Shibata, N.; Miwa, S.; Sawa, K.; Moriya, H.; Takahashi, M.; Murayama, T.; Tenma, N.
Highlights: Extensive literature survey on two-phase flow experiment using 12 m or longer vertical tube was conducted. Experiments were conducted on two-phase flow regime observation, void fraction and frictional pressure drop measurement over a long channel length under high-pressure brine conditions. The transition of flow regime took place at higher superficial gas velocity under brine conditions. Through drift-flux model analysis, change in gas velocity under brine conditions was confirmed. New frictional pressure drop model at high-pressure two-phase flow under brine conditions is proposed. Abstract: The offshore methane hydrate production test conducted in Japan has demonstrated a successful production of methane gas from marine gas hydrates using depressurization methods. The method produces methane gas by dissociating methane hydrate, which is stable at low temperature and high pressure conditions, by lowering the bottom-hole pressure in the wellbore. Under this method, stable control of bottom-hole pressure is necessary to ensure continuous methane gas production. Therefore, understanding the behavior of upward gas–liquid two-phase flow, involving gas-brine mixture, in a wellbore is essential for the proper pressure drop evaluation in the production line. In the present study, void fraction and frictional pressure drop behaviors under nitrogen-brine two-phase flow conditions is investigated using the high-pressure test facility of 52.7 mm inner diameter and 28 m height. The measured void fraction was assessed using drift-flux model, and the results showed that the decrease in bubble diameter under bubbly flow in gas-brine two-phase flow conditions resulted in decrease in bubble rise velocity and uniformity of bubble distribution. It was also found that, under bubbly flow in gas-brine mixture, the frictional pressure drop tends to further decrease with elevation. Based on these findings and obtained experimental dataset, the new frictional pressure model for gas-brine two-phase flow under high-pressure conditions is developed in the present study.